The effect of using the SWOM strategy on the achievement of Alfeqeh concepts among sixth-grade female students in Jordan - Awajan, Wafa Suleiman (Journal of Educational and Psychological Sciences, 2021)
The study aimed to investigate the effect of using the SWOM strategy on the achievement of Alfeqeh concepts among sixth-grade female students in Jordan. The quasi-experimental approach was used, and the study sample consisted of (n = 40) students. The people were chosen by a simple random method. The experimental sample was (n = 20) students, and the control sample (n = 20). An achievement test was prepared to measure the effect of using the SWOM strategy and the results were in favor of the experimental group. High-achieving and low-achieving female students and the study recommended the importance of adopting the SWOM strategy in teaching Islamic education subjects in particular and humanitarian and scientific investigations in general.